Determination of Four Bioactive Compounds in Herba artemisiae scopariae - Han, D.D.; Row, K.H. (Asian Journal of Chemistry, 2010)
A simple HPLC method was developed for the determination of chlorogenic acid, caffeic acid, scoparone and rutin in Herba artemisiae scopariae. Chromatographic separation was carried out on a C18 column (250 mm × 4.6 mm, 5 μm) with gradient elution. The mobile phase consisted of acetonitrile:water:acetic acid (25:75:0.1, v/v/v) (A) and acetonitrile/water (65:35, v/v) (B). The UV detection wavelength was set to 325 nm. Under optimal conditions, the four compounds were baseline separated within 20 min. The calibration curve was linear over the following range: 1-100 μg/mL for chlorogenic acid, caffeic acid and scoparone and 5-500 μg/ mL for rutin. The correlation coefficient of chlorogenic acid, caffeic acid, scoparone and rutin was 0.999, 0.999, 0.999 and 0.998, respectively. The detection limit (S/N = 3:1) was 0.03 μg/ mL for chlorogenic acid, scoparone and caffeic acid and 0.14 μg/mL for rutin. This method is simple and sensitive and has been applied successfully to determine the level of chlorogenic acid, caffeic acid and scoparone in Herba artemisiae scopariae.